(untitled) (International conference on multidisciplinary science, 2026)
Antibiotics are essential therapeutic agents in the treatment of bacterial infections. In recent years, the increasing resistance of microorganisms to antibiotics has become one of the most pressing challenges in global healthcare. This article analyzes the molecular-biological mechanisms of antibiotic resistance development in bacteria, the factors leading to the formation of resistant strains, and their significance in clinical practice. Furthermore, the importance of the rational use of antibiotics and the oversight of antimicrobial therapy are discussed.